2009
DOI: 10.1016/j.pain.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychological determinants of problematic outcomes following Total Knee Arthroplasty

Abstract: The primary objective of the present study was to examine the role of pain-related psychological factors in predicting pain and disability following Total Knee Arthroplasty (TKA). The study sample consisted of 75 (46 women, 29 men) individuals with osteoarthritis of the knee who were scheduled for TKA. Measures of pain severity, pain catastrophizing, depression, and pain-related fears of movement were completed prior to surgery. Participants completed measures of pain severity and self-reported disability 6 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
203
3
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(247 citation statements)
references
References 64 publications
19
203
3
15
Order By: Relevance
“…We found that preoperative depressive symptoms trajectories were not prognostic for the postoperative pain trajectories. Other reports found depressive symptoms to be prognostic for postoperative pain [5,6,12,17], but others did not [4,21,25]. We also found that patient depressive symptom scores did not improve after surgery.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We found that preoperative depressive symptoms trajectories were not prognostic for the postoperative pain trajectories. Other reports found depressive symptoms to be prognostic for postoperative pain [5,6,12,17], but others did not [4,21,25]. We also found that patient depressive symptom scores did not improve after surgery.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, depressive symptoms have been shown to decrease after surgery [5,6,12]. However, other studies have suggested depressive symptoms have little influence on pain or function postoperatively [21,25]. Our study was hypothesis-driven because several studies have reported inconsistent findings related to the prognostic value of preoperative depressive symptoms and the extent to which depressive symptoms change from the pre-to the postoperative period [5,6,12,16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that pain catastrophizing, greater medical comorbidity, lower educational attainment, depression, fear avoidance, and other psychologic factors are associated with persistent pain and/ or enhanced functional limitations after TKA [9,10,17,26,29,35]. Pain catastrophizing has been defined as ''an exaggerated negative mental set brought to bear during actual or anticipated painful experience'' [31].…”
Section: Introductionmentioning
confidence: 99%
“…Pain catastrophizing has been defined as ''an exaggerated negative mental set brought to bear during actual or anticipated painful experience'' [31]. Prior research on factors associated with persistent OA-related knee pain (lasting more than 6 months) found that pain catastrophizing explained a substantial proportion of variance in measures of pain, psychologic disability, and limitations in walking speed [27,29,30]. Similarly, worse mental health (including depression) and greater number of pain problems have been associated with worse THA and TKA outcomes [22,29,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation